HUBUNGAN PENGAWASAN PIMPINAN DENGAN EFEKTIVITAS KERJA APARATUR PEMERINTAH DAERAH DI BAGIAN TATA PEMERINTAHAN SEKRETARIAT DAERAH KABUPATEN SAMBAS - Lastri E.42009001 (FISIP Universitas Tanjungpura Pontianak, 2013)
This thesis is aimed to analyze the relationship between the leadership of the effectiveness of the surveillance apparatus in Bagian Tata Pemerintahan Sekretariat Daerah Sambas Regency. The title of this essay concerns raised by poor working effectiveness and the lack of oversight that most of the leadership at Bagian Tata Pemerintahan Sekretariat Daerah Sambas Regency, so in this paper will analyze whether there is a relationship between the effectiveness of supervisory leadership. This study uses a quantitative explanation of the pattern of associative interactive or reciprocal relationship. This research was conducted with several stages beginning with the pre research first, make a research design to proceed with the proposed research, to test the validity of data, followed by analyzing and collecting data both primary and secondary, and forwarded to a research report (thesis). Research sites in Bagian Tata Pemerintahan Sekretariat Daerah Sambas Regency. The samples were all employees at Bagian Tata Pemerintahan Sekretariat Daerah Sambas Regency, amounting to 9 people. The conclusion of this research is going strong and positive relationship between supervisory leadership to employee effectiveness in Bagian Tata Pemerintahan Sekretariat Daerah Sambas Regency. The level of the relationship between the leadership of the effectiveness of supervisory employees is 47.47% and the remaining 52.53% is determined by other factors not examined in this study as factors environmental characteristics, worker characteristics, organizational characteristics and management factors such as planning, organizing, actualizing that can support that level of effectiveness of employees in Bagian Tata Pemerintahan Sekretariat Daerah Sambas Regency is getting better.Keywords: Supervision Leadership, Work Effectiveness.